Korelasi kadar glukosa darah puasa dan derajat kepositifan bakteri tahan asam pada pasien tuberkulosis - Muslim, Azhari (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Hyperglycemia and impaired glucose regulation are associated with more severe pulmonary tuberculosis and higher sputum smear positivity grades. Objective: To determine the correlation between fasting blood glucose (FBG) levels and the degree of acid-fast bacilli (AFB) smear positivity among pulmonary tuberculosis patients at Sukamaju Primary Health Center, Bandar Lampung. Purpose: To determine the correlation between fasting blood glucose (FBG) levels and the degree of acid-fast bacilli (AFB) smear positivity among pulmonary tuberculosis patients. Method: An analytical cross-sectional study was conducted on 50 smear-positive pulmonary TB patients fulfilling the inclusion criteria, in whom FBG levels and AFB smear grading were measured and analyzed using Spearman’s rank correlation test with a 0.05 significance level. Results: Bivariate analysis demonstrated a significant positive correlation between FBG levels and AFB smear grading (r = 0,56; p < 0.05), indicating that higher FBG levels were associated with higher AFB smear positivity. Conclusion: There is a positive correlation between FBG levels and AFB smear positivity among pulmonary TB patients, highlighting the need for integrated glycemic screening and control within TB management at primary care level. Keywords: Acid-fast bacilli; Fasting blood glucose; Hyperglycemia; Pulmonary tuberculosis Pendahuluan: Hiperglikemia dan gangguan regulasi glukosa berhubungan dengan progresivitas tuberkulosis paru serta peningkatan derajat kepositifan sputum BTA Tujuan: Untuk mengetahui korelasi kadar glukosa darah puasa dengan derajat kepositifan BTA pada pasien tuberkulosis paru. Metode: Penelitian analitik dengan desain potong lintang pada 50 pasien TB paru BTA positif yang memenuhi kriteria inklusi dengan pemeriksaan GDP dan grading BTA, kemudian dianalisis dengan uji korelasi Spearman (α = 0.05). Hasil: Analisis bivariat menunjukkan korelasi positif bermakna antara kadar GDP dan derajat kepositifan BTA (r = 0.56; p < 0.05) yang mengindikasikan semakin tinggi kadar glukosa darah puasa, semakin tinggi derajat kepositifan BTA. Simpulan: Terdapat korelasi positif antara kadar glukosa darah puasa dan derajat kepositifan BTA pada pasien TB paru, sehingga skrining dan pengendalian glikemik perlu diintegrasikan dalam tata laksana TB di layanan primer. Kata kunci: Bakteri Tahan Asam; Glukosa darah puasa; Hiperglikemia; Tuberkulosis paru.